Seasonal ecophysiology of two páramo species: the dominance of light over water limitations - Sanchez, Adriana; Mercado, Lina M.; Posada, Juan M.; Smith, William Kirby (Frontiers in Plant Science, 2025)
Dry and rainy seasons in many ecosystems differ significantly in cloudiness, precipitation, and incident sunlight. These seasonal variations can influence photosynthesis by altering light availability and water stress. This study examines whether light availability or water stress is the primary limiting factor for photosynthesis in páramo plants during the dry and rainy seasons. We measured photosynthetic carbon gain per unit leaf area (An), stomatal conductance (gs), chlorophyll fluorescence (ϕPSII), and leaf water potentials, in two dominant páramo species, Espeletia grandiflora and Chusquea tessellata, across both seasons. Photosynthetic light-response curves were generated for each species, and statistical analyses assessed the relative influence of environmental factors such as light, temperature, and vapor pressure deficit on An. Contrary to our expectations, An was higher in the dry season despite increased water stress, suggesting that light availability is a stronger driver of carbon assimilation. However, light-response curves showed that Espeletia grandiflora exhibited higher potential carbon uptake during the dry season, while C. tessellata had greater uptake during the rainy season. Statistical analyses indicated that light was the primary factor influencing An in both seasons, though temperature and vapor pressure deficit also played a role for C. tessellata in the rainy season. The combination of high solar radiation and elevated leaf temperatures in the dry season facilitated greater carbon assimilation, particularly in E. grandiflora. In contrast, the cloudier conditions of the rainy season limited photosynthesis despite reduced water stress. Although C. tessellata exhibited high An during the dry season, it appeared vulnerable to high radiation and desiccation. These findings emphasize that cloud cover and light availability, rather than water stress alone, are key drivers of páramo plant carbon uptake, with important implications for predicting climate change effects in high-altitude ecosystems.